Fraud in letter of credit - Malaysian banks' perspective - Che Hashim, Rosmawani; Othman, Ahmad Azam; Abdul Aziz, Akhtarzaitie (2011)
Letter of credit (LC) is a payment mechanism in international trade which is claimed to provide utmost security to the contracting parties compared to other methods of payment. The security provided by this device however does not extend to fraud risk. The nature of LC transactions and rampant development in technology has opened a pathway for fraudster to capitalize on the dependence of the parties to the LC transactions on paper-based documentation. Since LC documents can be easily fabricated, there are many occasions in which the payment by LC was refused in introductory trade relationship due to suspicion of fraudulent documents. Moreover, the existence of fraud may destroy the smooth flow of LC procedure of payment and cause a disaster to the whole transaction. Consequently, fraud in LC transaction will frustrate the parties involved such as buyer, seller as well as banker. This paper aims to examine the fraud climate in LC transactions with special reference to Malaysian banks practices. Furthermore, it seeks to identify the modus operandi used by fraudsters in LC transactions in Malaysia. Last but not least, it highlights the actions undertaken by Malaysian banks in dealing with fraud in LC transactions. Due to lack of published materials and written information of this issue in Malaysia, interviews were conducted with LC’s key person and experts to explore the real situation. The finding of this study established that the phenomenon of fraud in LC transaction is not uncommon in Malaysia where its occurrence is marginal and not negligible.